Validitas Soal pada Asesmen Kompetensi Minimum Materi Ekologi SMA Kelas X - Marsi Sensus; Kasman Arifin; Asmawati Munir (Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Minimum Competency Assessment is an assessment of the basic competencies needed by students in developing their own capacity and positive participation in society. The assessment components measured are reading literacy and numeracy literacy. Most students in SMA and SMK are not ready with the Minimum Competency Assessment. Students assume that the questions tested are not in accordance with the learning material. Teachers must be able to familiarize students with literacy and make literacy questions correctly. This study aims to analyze the product of the Minimum Competency Assessment instrument developed. This type of research is research and development using 4D models. Validation was carried out on reading literacy questions, numeration related to high school ecology material for Class X. The results show that the number of items in the reading literacy question, numeracy question, choice question, and matchmaking question include the category of quite suitable to very suitable in terms of the number of question items. The number of questions in the complex multiple-choice section including the appropriate category (100%). Based on the validator's assessment, the Minimum Competency Assessment items developed are sufficient in accordance with the Basic Competencies of Class X High School Ecology Materials.